2019
DOI: 10.1080/1350293x.2019.1678926
|View full text |Cite
|
Sign up to set email alerts
|

Dutch early years classroom teachers facilitating and guiding musical play: problems and opportunities

Abstract: Musical play is an activity in which young children more or less freely explore and create with sound with limited guidance from a teacher. This study explored the occurrence of musical play in Dutch early years education (4-5 year olds). Twenty early years classroom teachers were interviewed about the content of the music education taking place in their classroom, and about a possible facilitation and guidance of musical play. Findings showed that ten teachers were unfamiliar with musical play, whilst nine ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
(35 reference statements)
0
4
0
Order By: Relevance
“…Musical capabilities of young children are enhanced by musically trained adults who facilitate an enabling environment (Bartel & Cameron, 2007; Custodero, 2005; Ilari, 2018; Marsh & Young, 2015; Nieuwmeijer et al, 2019; Trinick & Pohio, 2018; Young, 2005). The lack of national guidance or specific music curriculum (Southcott & de Vries, 2006) allocates music education to a tenuous position, depending on educators’ discretion, resulting in delivering poorly conceptualised, ineffective or tokenistic music learning experiences (Nyland et al, 2015; Suthers, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Musical capabilities of young children are enhanced by musically trained adults who facilitate an enabling environment (Bartel & Cameron, 2007; Custodero, 2005; Ilari, 2018; Marsh & Young, 2015; Nieuwmeijer et al, 2019; Trinick & Pohio, 2018; Young, 2005). The lack of national guidance or specific music curriculum (Southcott & de Vries, 2006) allocates music education to a tenuous position, depending on educators’ discretion, resulting in delivering poorly conceptualised, ineffective or tokenistic music learning experiences (Nyland et al, 2015; Suthers, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Teachers' knowledge is not always related to their level of education, nor guarantee that teachers have content knowledge related to effective teaching (Piasta et al, 2006). The most common challenges include early childhood teachers that hold limited content knowledge (Nieuwmeijer et al, 2019;Nieuwmeijer & van Oers, 2021;Lindeman et al, 2021;Hesterman & Targowska, 2020;Zhu et al, 2021). This contradicts Fleer's (2010) study which demonstrating that some teachers may have the requisite content knowledge, but they did not always make concepts conscious to children while engaged in play-learning programs they planned.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, previous studies gave a comprehensive review of teachers' knowledge. Nieuwmeijer et al (2019) recognized that musical play is a valuable addition to the early years of music education, one that enables young children to learn about music more consistently with their age and interests. This is supported by Nieuwmeijer and van Oers (2021) who revealed that taking part in the PD promoted teachers' TE for the musical play and 50% of the respondents for music education in general.…”
Section: Professional Development (12 Articles)mentioning
confidence: 99%
See 1 more Smart Citation